Cloning and location of a gene governing lysine epsilon-aminotransferase, an enzyme initiating beta-lactam biosynthesis in Streptomyces spp. - Madduri, K (1991)
In actinomycetes that produce beta-lactam antibiotics of the cephem type, lysine epsilon-aminotransferase is the initial enzyme in the conversion of lysine to alpha-aminoadipic acid. We used a two-stage process ("chromosome walking") to screen a lambda library of Streptomyces clavuligerus genomic DNA for fragments that expressed lysine epsilon-aminotransferase activity in S. lividans. Restriction analysis of the cloned DNA confirmed the location of the putative lat gene within the cluster of beta-lactam biosynthesis genes, roughly midway between pcbC, the structural gene for isopenicillin N synthetase, and the putative cefE gene encoding deacetoxycephalosporin C synthetase.